The Resurrection of Jesus in the Pre-Pauline Formula of 1 Cor 15.3–5 - Ware, James P. (New Testament studies, 2014)
The present essay offers a fresh contribution to the long-standing debate regarding the nature of the resurrection of Christ within the pre-Pauline formula of 1 Cor 15.3–5. The article first provides an analysis of the current state of the discussion, offering new observations and lines of evidence which suggest that a number of common arguments on both sides of the debate are lacking or inconclusive. The essay then offers a new proposal regarding the verb used within the formula for the resurrection event. The article presents previously neglected evidence significant for the debate regarding Jesus' resurrection within this primitive confession.